The reality of continuous formation from the point of view of the physical and sports education professors in the secondary education stage - Khaladi , mourad (sports creativity, 2025)
The study aims at identifying the reality of continuous formation from the point of view of the teachers of physical and sports education, as well as to reach an understanding the differences in the direction of continuous formation according to the variables of study (age, scientific qualification, seniority in teaching), on a sample formed from (40) teachers of physical and sports education in secondary education. They were chosen in a random way , and the researcher adopted the descriptive analytical approach , and for study tools the researcher used a scale of 32 paragraphs, distributed among four areas: Planning, implementation, evaluation, classroom. The results of the study showed there are no statistically significant differences between teachers' answer averages in the direction of continuous formation due to study variables (age, scientific qualification, seniority in teaching).